Carbon-ceramic composite material, preparation method thereof and carbon-ceramic brake disc
By mixing silicon carbide, carbon fiber and additives evenly, and using DC rapid sintering process to sinter, the problems of uneven distribution of preformed materials and unstable high-temperature mechanical properties in the preparation of carbon ceramic composite materials are solved, and carbon ceramic composite materials are realized The preparation of uniform phase and high temperature performance is good.
Patent Information
- Application Number
- CN202411595805.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing carbon ceramic composite material preparation process has problems such as uneven distribution of prefabricated materials, unstable friction performance, poor mechanical properties and unstable high-temperature mechanical properties.
A uniform powder is used to mix silicon carbide, carbon fiber and additives, and sintering is carried out through a DC rapid sintering device, pressure and heating are applied, and the temperature is gradually increased to high temperature insulation to prepare carbon ceramic composite materials.
The prepared carbon ceramic composite material has uniform phase, good high temperature performance, excellent mechanical properties, stable friction performance, and high density, and is suitable for a wide range of applications.
Smart Images

Figure CN119430971A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, in particular to a carbon-ceramic composite material and a preparation method thereof and a carbon-ceramic brake disc. Background Art
[0002] With the development of modern transportation, in order to ensure the safety of the braking system and the reliability of friction transmission, the requirements for the braking system are more stringent, requiring a high and stable friction coefficient; good wear resistance; strong environmental adaptability; stable high-temperature mechanical properties; stable friction process and low noise; low cost, simple process, environmental protection and reliability.
[0003] The previous powder metallurgy metal friction materials can no longer meet the requirements. Carbon-ceramic composite materials were used as aircraft structural parts in the early days. They have been used in the friction field since the 1990s. They are currently widely used in new energy vehicles, high-end fuel vehicles, and modified vehicles.
[0004] Reaction melt infiltration (RMI) is the mainstream carbon ceramic brake disc production process in the market. According to the different preforms, it is divided into short-fiber carbon ceramic discs and long-fiber carbon ceramic discs. Using a vacuum sintering furnace, a layer of silicon powder is spread on the surface of the prepared preform. After heating to 1400℃~1500℃, the silicon powder melts, and the liquid silicon penetrates into the interior of the preform through capillary action, and reacts chemically with the preform to form silicon carbide. This method is a relatively simple process for preparing carbon ceramics, but there are too many processing steps, and some problems caused by this limit the promotion of carbon ceramic brake discs. Among them, it is mainly caused by two aspects. One of them is the preparation of the preform: the material distribution uniformity of the short fiber molded preform is poor, so after the carbon ceramic disc is made, the surface friction performance is unstable and the mechanical properties are poor; after the needle-punched preform is surface coated by the CVI process, the graphite film in some areas will be uneven, blocking the passage and affecting the infiltration of the next liquid silicon. The difference in structure between carbon felt and non-woven cloth leads to the use of carbon felt as a friction layer, and its service life is limited; the other is the residual silicon in the physical phase. The melting point of silicon is only 1410℃, which affects the stability of the high-temperature mechanical properties and the surface friction performance of the carbon ceramic brake disc, and the silicon carbide generated by the reaction will block the passage, resulting in the influence of infiltration. Summary of the invention
[0005] The technical problem to be solved by the embodiments of the present invention is to provide a carbon-ceramic composite material and a preparation method thereof and a carbon-ceramic brake disc, which can shorten the processing time, and the prepared carbon-ceramic composite material has a uniform phase and good high-temperature performance.
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a carbon-ceramic composite material, which comprises the following steps: uniformly mixing silicon carbide, carbon fiber and an additive to obtain a carbon-ceramic preformed powder; placing the carbon-ceramic preformed powder in a mold of a direct current rapid sintering device, applying a first preparation operation means, and obtaining a sample to be sintered; starting a heating system of the direct current rapid sintering device, gradually increasing the direct current for heating, and after heating to a first temperature, applying a second preparation operation means to the sample to be sintered, continuing to increase the direct current, and then gradually heating to a second temperature, and keeping the temperature for a period of time; closing the heating system, cooling naturally, and obtaining the carbon-ceramic composite material.
[0007] In a feasible implementation, the first preparation method includes: selecting a mold of suitable size, isolating the inside with graphite paper, loading the carbon ceramic prefabricated powder into the mold, applying a pressure of 1 to 5 MPa to pre-compact it, and wrapping it with thermal insulation carbon felt.
[0008] In a feasible implementation, the second preparation operation means includes: gradually applying pressure to the mold at a pressure increase rate of (1-10) MPa / min, until the pressure reaches (30-50) MPa.
[0009] In a feasible implementation, the auxiliary agent is selected from at least one of Al4SiC, B4C or a metal oxide mixture; wherein the metal oxide mixture includes at least a first metal oxide and a second metal oxide; the first metal oxide is selected from at least one of Al2O3 and Y2O3, and the second metal oxide is selected from at least one of MgO, CaO, La2O3, Sc2O3 and Er2O3.
[0010] In a feasible implementation, the mass ratio of the silicon carbide, carbon fiber and additive is 1:(0.5-2):(0.01-0.1).
[0011] In a feasible implementation, the length of the carbon fiber is 5 mm to 30 mm.
[0012] In a feasible implementation, the first temperature range is 700° C., and the heating rate is 50-100° C. / min.
[0013] In a feasible implementation, the second temperature range is: 1600°C to 2100°C; the heating rate for gradually heating to the second temperature is: 10 to 50°C / min; and the insulation time is 20 minutes to 2 hours.
[0014] Correspondingly, the present invention also provides a carbon-ceramic composite material, which is prepared by any of the preparation methods described above.
[0015] Correspondingly, the present invention also provides a carbon-ceramic brake disc, which is prepared using the above-mentioned carbon-ceramic composite material.
[0016] The implementation of the present invention has the following beneficial effects:
[0017] The preparation method of the carbon-ceramic composite material provided in the embodiment of the present application uses silicon carbide powder and carbon fiber staple fibers as raw materials, mixes them to form a uniform powder, uses a flash firing process, and directly sintered. The preparation process is simple, low-cost, and short in time. In addition, the raw materials used in the preparation method provided in the embodiment of the present application do not use silicon monomers, and there is no need to melt silicon into liquid silicon, and no infiltration process is required. It is precisely because it does not contain free silicon that the carbon-ceramic composite material prepared by the preparation process provided in the present application has good high-temperature performance. At the same time, since the raw materials and preparation process of the embodiment of the present application are simple, the raw materials can be mixed evenly, and the carbon-ceramic composite material finally prepared has a uniform phase distribution and good mechanical properties, which is conducive to a wide range of applications.
[0018] The carbon-ceramic composite material provided in the embodiments of the present application has the advantages of uniform phase, excellent mechanical properties, stable friction performance, high temperature resistance, high density, etc., and is conducive to a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a SEM image of the fracture surface of the carbon-ceramic composite material prepared in Example 1 (1000 times);
[0020] Figure 2 This is a SEM image (5000 times) of the fracture surface of the carbon-ceramic composite material prepared in Example 1;
[0021] Figure 3 This is an EDS layered image of the carbon-ceramic composite material prepared in Example 1;
[0022] Figure 4 EDS layered image of the carbon-ceramic composite material prepared in Example 1 - C;
[0023] Figure 5 This is the EDS layered image of the carbon-ceramic composite material prepared in Example 1 - Si. DETAILED DESCRIPTION
[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0026] The present invention provides a method for preparing a carbon-ceramic composite material. The method for preparing the carbon-ceramic composite material comprises the following steps:
[0027] S110, mixing silicon carbide, carbon fiber and additives uniformly to obtain carbon ceramic prefabricated powder.
[0028] Wherein, the operation of uniformly mixing silicon carbide, carbon fiber and auxiliary agent can be to add silicon carbide, carbon fiber and auxiliary agent into a stirring device at the same time and stir them evenly, and the raw materials are evenly distributed by stirring. Optionally or preferably, the auxiliary agent and carbon fiber can be mixed evenly first, and then silicon carbide powder can be added. Optionally or preferably, the auxiliary agent and silicon carbide powder can be mixed evenly first, and then carbon fiber can be added. In this way, it is conducive to the full mixing of the raw materials, and then conducive to the uniform distribution of the physical phase of the final product.
[0029] Furthermore, in a feasible embodiment, the auxiliary agent is selected from at least one of Al4SiC, B4C or a metal oxide mixture; wherein the metal oxide mixture includes at least a first metal oxide and a second metal oxide; the first metal oxide is selected from at least one of Al2O3 and Y2O3, and the second metal oxide is selected from at least one of MgO, CaO, La2O3, Sc2O3 and Er2O3.
[0030] Optionally or preferably, the metal oxide mixture is selected from at least one of the following combinations: Al2O3 and Y2O3; Al2O3 and CaO; Al2O3 and MgO; Al2O3, Y2O3, MgO and CaO; Y2O3 and La2O3; Y2O3 and S2O3; or Al2O3 and Er2O3.
[0031] Optionally or preferably, the metal oxides are mixed into a mixture of Al2O3 and Y2O3. Al2O3 and Y2O3 can form a yttrium aluminum garnet (YAG) liquid phase at 1760°C to promote densification. Further, the molar ratio of Al2O3 to Y2O3 is 1:(0.4-0.6).
[0032] Optionally or preferably, the metal oxides are mixed into a mixture of Al2O3 and CaO. Al2O3 and CaO form a liquid phase at 1360-1500°C to promote densification. Further, the molar ratio of Al2O3 to CaO is 1:(0.8-1.2).
[0033] Optionally or preferably, the metal oxides are mixed into a mixture of Al2O3 and MgO. Al2O3 and MgO generate magnesium aluminum spinel at 1450-1600°C, generate a liquid phase, and promote densification. Further, the molar ratio of Al2O3 to MgO is 1:(0.4-0.6).
[0034] Optionally or preferably, the metal oxide mixture is a mixture of Al2O3, Y2O3, MgO and CaO. Al2O3, Y2O3, MgO and CaO can work together to generate a liquid phase and promote densification. Further, the molar ratio of Al2O3, Y2O3, MgO and CaO is 1: (0.4-0.6): (0.1-0.2): 0.1.
[0035] Optionally or preferably, the metal oxide mixture is a mixture of Y2O3 and La2O3. When the mixture of Y2O3 and La2O3 is above 2000°C, the rare earth elements can react with oxygen on the surface of silicon carbide to reduce the oxygen content, promote densification, and improve thermal conductivity. Furthermore, the molar ratio of Y2O3 to La2O3 is (0.4-0.6):1.
[0036] Optionally or preferably, the metal oxide mixture is a mixture of Y2O3 and S2O3. The rare earth elements of the mixture of Y2O3 and S2O3 can react with oxygen on the surface of silicon carbide at a temperature above 2050°C, reduce the oxygen content, promote densification, and improve thermal conductivity. Furthermore, the molar ratio of Y2O3 to S2O3 is (0.2-0.4):1.
[0037] Optionally or preferably, the metal oxide mixture is a mixture of Al2O3 and Er2O3. The mixture of Al2O3 and Er2O3 can form Er3Al5O 12 , promoting grain refinement and improving performance. Further, the molar ratio of Al2O3 to Er2O3 is (0.4-0.6):1.
[0038] Optionally or preferably, the auxiliary agent is Al4SiC. Al4SiC has low density and high melting point, decomposes at 1700°C, carbon can promote grain refinement, and Al activator enhances grain boundary diffusion.
[0039] Optionally or preferably, the auxiliary agent is B4C. B4C can form a eutectic phase with silicon carbide to promote densification.
[0040] In a feasible embodiment, optionally or preferably, the mass ratio of silicon carbide, carbon fiber and additive is 1: (0.5-2): (0.01-0.1). The mass ratio of silicon carbide, carbon fiber and additive is 1: (0.5-1.5): 0.05. Optionally or preferably, the mass ratio of silicon carbide, carbon fiber and additive is 1: 0.5: 0.05, 1: 1: 0.05 or 1: 1.5: 0.05.
[0041] In a feasible embodiment, the length of the carbon fiber is 5 mm to 30 mm. Optionally or preferably, the length of the carbon fiber is 10 to 25 mm. Optionally or preferably, the length of the carbon fiber is 10 to 20 mm. Optionally or preferably, the length of the carbon fiber is 10 mm, 15 mm or 20 mm. Optionally or preferably, the length of the carbon fiber is 15 mm.
[0042] S120, placing the carbon ceramic prefabricated powder in a mold of a direct current rapid sintering device, applying a first preparation operation means, and obtaining a sample to be sintered.
[0043] In a feasible embodiment, the first preparation means includes: selecting a mold of suitable size, isolating the inside with graphite paper, loading the carbon ceramic prefabricated powder into the mold, applying a pressure of 1 to 5 MPa for pre-compression and compaction, and wrapping the heat-insulating carbon felt. Pre-compression and compaction can significantly increase the initial density of the sample and reduce the porosity. High-density samples are more likely to form a dense structure during DC rapid sintering, improving the mechanical strength and durability of the material. Pre-compression and compaction can reduce the pores and voids in the sample and make the material more uniform. The uniform structure reduces the generation of cracks and defects and improves the overall performance and reliability of the material. Pre-compression and compaction can make the sample better formed in the mold and ensure the consistency of shape and size. Consistent shape and size are helpful for subsequent processing and application, and improve the qualified rate and production efficiency of the product. Pre-compression and compaction help to evenly distribute fillers and additives in the sample. Evenly distributed fillers and additives can better play their functions and improve the comprehensive properties of the material, such as electrical conductivity and thermal conductivity. Pre-compressed and compacted samples have higher density and fewer pores, and a shorter heat conduction path. During rapid sintering or flash sintering, heat can be transferred more evenly to the inside of the sample, avoiding local overheating and uneven sintering. Pre-compression and compaction can enhance the interface bonding between carbon fiber and other fillers. Good interface bonding can improve the mechanical properties and fatigue resistance of the material. Pre-compression and compaction can make the sample surface smoother and flatter. A smooth surface helps to improve the appearance quality of the material and reduce surface defects, thereby improving the market competitiveness of the product.
[0044] S130, starting the heating system of the DC fast sintering device, gradually increasing the DC current for heating, after heating to the first temperature, applying the second preparation operation means to the sample to be sintered, continuing to increase the DC current, and then gradually raising the temperature to the second temperature, and keeping the temperature for a period of time.
[0045] Furthermore, the rate of increase of the DC current is 1000 A per minute. The increase of the DC current here refers to increasing the DC current loaded on both ends of the mold of the DC rapid sintering device, that is, directly acting on both ends of the carbon ceramic preformed powder. The carbon ceramic preformed powder is heated by the DC current.
[0046] In a feasible embodiment, the second preparation operation means includes: gradually applying pressure to the mold at a pressure increase rate of 10MPa / min to a pressure of 30MPa to 50MPa. Rapid pressure increase causes rapid changes in pressure inside and outside the material, resulting in large thermal and mechanical stresses. These stresses may cause cracks, delamination or fractures inside the material, seriously affecting the mechanical strength and integrity of the material. Rapid pressure increase may cause gas to dissolve or escape rapidly inside the material. Uneven gas dissolution and escape may form bubbles or holes inside the material, reducing the density and mechanical properties of the material. Rapid pressure increase may cause uneven phase change inside the material. Different regions may undergo different phase change processes, resulting in uneven microstructure of the material, affecting its physical and chemical properties. Rapid pressure increase may prevent certain chemical reactions from fully proceeding. Incompletely reacted substances may remain in the material, affecting the purity and performance of the material, and even causing subsequent instability and degradation. Rapid pressure increase can cause excessive pressure gradients inside and outside the material. This pressure gradient may cause stress concentration inside the material, increasing the risk of cracks and defects. Rapid pressure increase may cause the surface pressure of the material to increase rapidly, while the internal pressure lags behind. This pressure difference may cause the expansion coefficients of the surface and the interior of the material to be different, causing internal stress and further increasing the risk of cracks. Rapid pressure increase may prevent the material from being fully densified during the sintering process. The density of the material decreases and the porosity increases, resulting in a decrease in mechanical properties. Rapid pressure increase places higher pressure resistance and safety requirements on the equipment. If the equipment cannot withstand the pressure changes caused by rapid pressure increase, it may cause equipment damage or safety accidents. However, too slow a pressure increase rate will significantly increase the time of the entire heat treatment process. The production cycle is extended, resulting in reduced production efficiency and increased production costs. Long-term pressure increase process consumes more energy. Increased energy consumption and rising production costs do not meet the requirements of energy conservation and emission reduction. Although slow pressure increase helps the gradual escape of volatile substances, if the pressure increase is too slow, these substances may begin to escape at a lower pressure, resulting in incomplete escape. Residual volatile substances may re-condense or react in the subsequent high-pressure stage, affecting the purity and performance of the material. Too slow a pressure increase rate may cause uneven structural changes in the material at different stages. The microstructure and properties of the material may vary in different areas, affecting the overall uniformity and consistency. A pressurization rate that is too slow may cause pyrolysis products (such as gases and liquids) to begin to form at lower pressures, but the discharge rate is slow. These products may accumulate inside the material, resulting in increased porosity, affecting the density and mechanical properties of the material. A pressurization rate that is too slow may result in weak interfacial bonding inside the material. Poor interfacial bonding will affect the mechanical properties and durability of the material. A pressurization rate that is too slow will cause the equipment to run longer under high pressure. The utilization rate of the equipment is reduced and the maintenance cost is increased. A pressurization rate that is too slow may make temperature control more difficult because the changes in temperature and pressure need to be coordinated.Improper temperature control may affect the performance and quality of the material.
[0047] In a feasible implementation, the first temperature range is: 700°C, and the heating rate is 50°C / min to 100°C / min. The sintering temperature is determined according to different sintering aids. If the temperature is not appropriate, the product cannot be formed or has poor performance.
[0048] In a feasible embodiment, the second temperature range is: 1600℃~2100℃. The heating rate of gradually heating to the second temperature is: 10℃ / min~50℃ / min. If the heating rate is too fast, the product will have a local temperature that is too high, affecting the performance, and if it is too slow, it will affect the efficiency. A too slow heating rate will significantly increase the time of the entire heat treatment process. The production cycle is extended, resulting in reduced production efficiency and increased production costs. A long heating process consumes more energy. Energy consumption increases and production costs rise, which does not meet the requirements of energy conservation and emission reduction. Although slow heating helps the gradual escape of volatile substances, if the temperature rises too slowly, these substances may begin to volatilize at a lower temperature, resulting in incomplete escape. Residual volatile substances may re-condense or react in subsequent high-temperature stages, affecting the purity and performance of the material. Too slow a heating rate may cause uneven structural changes in the material at different stages. The microstructure and properties of the material may differ in different regions, affecting the overall uniformity and consistency. Too slow a heating rate may cause pyrolysis products (such as gas and liquid) to start to form at a lower temperature, but the discharge rate is slow. These products may accumulate inside the material, resulting in an increase in porosity, affecting the density and mechanical properties of the material. Too slow a heating rate may result in a weak interface bonding inside the material. Poor interface bonding will affect the mechanical properties and durability of the material. Too slow a heating rate will cause the equipment to run longer at high temperatures. The utilization rate of the equipment will decrease and the maintenance cost will increase. At the same time, rapid heating will increase the temperature difference between the inside and outside of the material, resulting in greater thermal stress. Thermal stress may cause cracks, delamination or fracture inside the material, seriously affecting the mechanical strength and integrity of the material. Rapid heating will cause volatile substances (such as moisture, solvents, etc.) inside the material to vaporize rapidly. The gas cannot escape in time, and bubbles or holes may form inside the material, reducing the density and mechanical properties of the material. Rapid heating may cause uneven phase change inside the material. Different regions may undergo different phase change processes, resulting in uneven microstructure of the material, affecting its physical and chemical properties. Rapid heating may cause pyrolysis products (such as gas and liquid) to be generated rapidly inside the material. These products may not be discharged in time, resulting in increased pressure inside the material, causing cracks or other defects. Rapid heating causes the surface temperature of the material to rise rapidly, while the internal temperature lags behind. This temperature difference may cause the expansion coefficients of the surface and the interior to be different, causing internal stress and further increasing the risk of cracks. Rapid heating may prevent the material from being fully densified during the sintering process. The density of the material decreases and the porosity increases, resulting in decreased mechanical properties. Although rapid heating can shorten the heating time, it may result in energy waste. Excessively high heating rates may reduce the energy efficiency of the equipment and increase production costs. Furthermore, the selection of the second temperature depends on the type and proportion of the additives.
[0049] In a feasible implementation, the holding time is 20 minutes to 2 hours. Furthermore, the holding time needs to be adjusted accordingly according to different additives and parameter conditions.
[0050] The DC rapid sintering device includes a pressurizing device, a vacuum chamber, a heating system, a high-voltage DC flash power supply, a control system, and a cooling system. The raw materials are placed in a mold composed of high-temperature ceramics and graphite, located in the center of the vacuum chamber, and are constrained by the pressure of the pressurizing system; the heating system enters the vacuum chamber through the outer wall of the vacuum chamber to heat the carbon ceramic preformed powder; the high-voltage DC flash power supply applies voltage to the graphite mold through the water-cooled copper electrodes at the upper and lower pressure heads of the pressurizing device; when in use, the heating element of the auxiliary heating system provides the required temperature for preheating the carbon ceramic preformed powder before flashing, and a certain pressure is applied through the pressurizing device; when the temperature reaches the set value, the high-voltage DC flash power supply applies a DC electric field to form flashing, so as to realize the low-temperature rapid densification of the carbon ceramic preformed powder; the high-voltage DC flash power supply is controlled by a program, and switches from voltage control to current control when flashing occurs, and ends heating after a certain period of time, and then cools to room temperature.
[0051] S140, turning off the heating system and cooling naturally to obtain a carbon-ceramic composite material.
[0052] The preparation method of the carbon-ceramic composite material provided in the embodiment of the present application uses silicon carbide powder and carbon fiber staple fibers as raw materials, mixes them to form a uniform powder, uses a flash firing process, and directly sintered. The preparation process is simple, low-cost, and short in time. In addition, the raw materials used in the preparation method provided in the embodiment of the present application do not use silicon monomers, and there is no need to melt silicon into liquid silicon, and no infiltration process is required. It is precisely because it does not contain free silicon that the carbon-ceramic composite material prepared by the preparation process provided in the present application has good high-temperature performance. At the same time, since the raw materials and preparation process of the embodiment of the present application are simple, the raw materials can be mixed evenly, and the carbon-ceramic composite material finally prepared has a uniform phase distribution and good mechanical properties, which is conducive to a wide range of applications.
[0053] In addition, the preparation method of the carbon-ceramic composite material provided in the embodiment of the present application is simple, convenient and low in cost in terms of raw material acquisition. Relying on the development of domestic carbon fiber, carbon fiber staple fibers are guaranteed in terms of price, supply and performance. The development of the photovoltaic industry has led to a stable supply of micron-level silicon carbide powder, so it is more convenient and cheap in terms of raw material acquisition and cost compared to the prior art; the preparation method of the carbon-ceramic composite material provided in the embodiment of the present application does not require the preparation of a preform, has fewer steps, and greatly shortens the preparation time and cost. The preparation method of the carbon-ceramic composite material provided in the embodiment of the present application is short in preparation time and can be completed in only a few hours. The rapid hot pressing (FHP) process is used, and a DC power supply forms a DC electric field to assist sintering, prevent grain growth, and obtain better mechanical properties. The preparation method of the carbon-ceramic composite material provided in the embodiment of the present application does not require reaction participation. The present invention uses silicon carbide powder for direct sintering, and does not require reaction participation during the sintering process. Therefore, there is no low melting point component in the phase that affects the high temperature performance. The prior art requires the limitation of a preform, which will lead to uneven physical phases of the finished product and unstable surface friction performance after long-term use. The carbon-ceramic composite material prepared by the method for preparing the carbon-ceramic composite material provided in the embodiment of the present application has high stability in mechanical properties and friction performance. The carbon-ceramic composite material prepared by the method for preparing the carbon-ceramic composite material provided in the embodiment of the present application has high density, and the density of the sintered sample of the present invention is close to complete density, which avoids the formation of defects in the sample due to pores, resulting in reduced performance.
[0054] The prior art prepares a preform, then uses reactive melt infiltration (RMI) to melt silicon into liquid and infiltrate it into the preform, generates silicon carbide through reaction, and obtains carbon ceramic material after cooling; the present invention uses a rapid hot pressing (FHP) process to directly press the prepared powder into carbon ceramic material, shortening the preparation time from one week to a few hours.
[0055] The existing carbon ceramic materials made by reactive melt infiltration (RMI) have a large number of pores in the sample, which cannot be completely dense, and there is a large amount of unreacted silicon inside, which affects the mechanical properties and surface friction properties of the material. The present invention directly sintered the silicon carbide powder through the rapid hot pressing (FHP) process, and it has a good combination with the carbon fiber surface, the density is close to completely dense, and there is no reaction involved, and there is no unreacted silicon affecting the performance.
[0056] The carbon ceramic material produced by the prior art has unstable surface friction performance due to the structural problem of the preform, and only the surface layer can be used as a friction material. After being worn away during use, the surface friction performance becomes unstable, affecting the use. However, because the present invention is powder sintering, there is no structural difference, and the usable volume is much larger than that of the prior art.
[0057] Accordingly, the embodiment of the present application also provides a carbon-ceramic composite material. The carbon-ceramic composite material is prepared by any of the preparation methods described above. The carbon-ceramic composite material provided by the embodiment of the present application has the advantages of uniform phase, excellent mechanical properties, stable friction performance, high temperature resistance, high density, etc., which is conducive to a wide range of applications.
[0058] Accordingly, the embodiment of the present application also provides a carbon-ceramic brake disc. The carbon-ceramic brake disc is prepared by using the above-mentioned carbon-ceramic composite material. The carbon-ceramic brake disc described in the embodiment of the present application has all the advantages of the above-mentioned carbon-ceramic composite material, which will not be repeated here.
[0059] With reference to the above implementation contents, in order to make the technical solution of the present application more specific, clear and easy to understand, the technical solution of the present application is now exemplified. However, it should be noted that the contents to be protected by the present application are not limited to the following embodiments.
[0060] Example 1
[0061] Silicon carbide, carbon fiber and additive B4C are uniformly mixed in a ratio of 1:0.66:0.05 to obtain carbon ceramic preformed powder;
[0062] A mold with an inner diameter of 80 mm was selected, the inside of which was insulated with graphite paper, the carbon ceramic prefabricated powder was loaded into the mold, a pressure of 5 MPa was applied to pre-press and compact it, and the heat-insulating carbon felt was wrapped to serve as the sample to be sintered;
[0063] Apply 5MPa pre-pressure to the sample to be sintered, adjust the infrared ray to align with the temperature measuring hole. Start the heating system, increase the current by 1000A per minute, heat to 700℃, apply 50MPa pressure to the mold at a pressure increase rate of 5MPa / min, increase the temperature at a heating rate of 50℃ / min, increase the temperature to 1900℃, and keep it warm for 30min;
[0064] After sintering, the heating system is turned off and the sintered sample is allowed to cool naturally in the mold to obtain a carbon-ceramic composite material.
[0065] Figure 1 This is a SEM image of the fracture surface of the carbon-ceramic composite material prepared in Example 1 (1000 times);
[0066] Figure 2 This is a SEM image (5000 times) of the fracture surface of the carbon-ceramic composite material prepared in Example 1;
[0067] Figure 3 This is an EDS layered image of the carbon-ceramic composite material prepared in Example 1;
[0068] Figure 4 EDS layered image of the carbon-ceramic composite material prepared in Example 1 - C;
[0069] Figure 5 This is the EDS layered image of the carbon-ceramic composite material prepared in Example 1 - Si.
[0070] Example 2
[0071] The method is basically the same as Example 1, except that the mass ratio of silicon carbide, carbon fiber and additive B4C is 1:1:0.05.
[0072] Example 3
[0073] The method is basically the same as Example 1, except that the mass ratio of silicon carbide, carbon fiber and additive B4C is 1:2:0.05.
[0074] Example 4
[0075] It is basically the same as Example 1, except that the additive is a metal oxide mixture, the metal oxide mixture is a mixture of Al2O3 and Y2O3, the molar ratio of Al2O3 and Y2O3 is 1:0.55, the mass ratio of silicon carbide, carbon fiber and additive is 1:2:0.05, and after heating to 700°C, a pressure of 40MPa is applied to the mold at a pressure increase rate of 5MPa / min, and the temperature is increased at a heating rate of 30°C / min to 1600°C and kept warm for 20min.
[0076] Example 5 is basically the same as Example 1, except that the auxiliary agent is a metal oxide mixture, the metal oxide mixture is a mixture of La2O3 and Y2O3, the molar ratio of La2O3 and Y2O3 is 1:0.35, and the mass ratio of silicon carbide, carbon fiber and auxiliary agent is 1:2:0.05. After heating to 700°C, a pressure of 40MPa is applied to the mold at a pressure increase rate of 10MPa / min, and the temperature is increased at a heating rate of 30°C / min to 2100°C and kept warm for 2h.
[0077] Example 6
[0078] It is basically the same as Example 4, except that the mass ratio of silicon carbide, carbon fiber and additive is 1:2:0.01.
[0079] Example 7
[0080] It is basically the same as Example 4, except that the mass ratio of silicon carbide, carbon fiber and additive is 1:2:0.1.
[0081] Example 8
[0082] It is basically the same as Example 4, except that after heating to 700°C, a pressure of 40MPa is applied to the mold at a pressure increase rate of 10MPa / min, the temperature is increased at a heating rate of 50°C / min to 1700°C, and the temperature is kept at this temperature for 20 minutes.
[0083] Example 9
[0084] It is basically the same as Example 4, except that the additive is a metal oxide mixture, the metal oxide mixture is a mixture of Al2O3, Y2O3, MgO, and CaO, the molar ratio of Al2O3, Y2O3, MgO, and CaO is 1:0.55:0.15:0.1, and the mass ratio of silicon carbide, carbon fiber, and additive is 1:2:0.05. After heating to 700°C, a pressure of 40MPa is applied to the mold at a pressure increase rate of 5MPa / min, and the temperature is increased at a heating rate of 30°C / min to 1800°C and kept warm for 20min.
[0085] Example 10
[0086] It is basically the same as Example 4, except that the auxiliary agent is Al4Si3C. After heating to 700°C, a pressure of 40MPa is applied to the mold at a pressure increase rate of 5MPa / min, and the temperature is increased at a heating rate of 30°C / min to 1750°C and kept warm for 20 minutes.
[0087] Comparative Example 1
[0088] Using carbon fiber staple as raw material and phenolic resin as adhesive, a preform is made by molding and carbonized at 900-1000°C, a process that usually takes several hours to several days. It is then siliconized by the RMI process, a process that usually takes 3-7 days.
[0089] Comparative Example 2
[0090] Using long fibers as raw materials, a 2.5D fiber preform is made through a needle punching process, and then densified by CVI or liquid phase impregnation. It is carbonized at 900-1000°C. CVI densification takes about a week, while liquid phase impregnation densification takes 2-3 days. Then, silicon is infiltrated using the RMI process, which usually takes 3-7 days.
[0091] Performance Testing
[0092] 1. Relative density (%) and density (g / cm 3 );
[0093] 2. Measure the surface hardness (HV) at a pressure of 1 to 5 kg according to GB / T 16534-2009 "Test Method for Hardness of Fine Ceramics at Room Temperature";
[0094] 3. Measure the flexural strength (MPa) according to GB / T 6569 fine ceramic flexural strength test method;
[0095] The performance test results are shown in the following table:
[0096]
[0097] It can be seen from the above table that the carbon-ceramic composite materials prepared in Examples 1 to 10 have better properties than the carbon-ceramic composite materials prepared in Comparative Examples 1 and 2.
[0098] From the above table and Figures 1 to 5 It can be seen that in the carbon-ceramic composite material prepared in Example 1, the carbon fibers are evenly dispersed, presenting a scattered and non-directional distribution, with high density and no obvious pores or defects. The carbon-ceramic composite material prepared in Example 1 has better performance than the carbon-ceramic composite materials prepared in other examples.
[0099] The basic concepts have been described above. Obviously, for those skilled in the art, the above detailed disclosure is only for example and does not constitute a limitation of this specification. Although not explicitly stated here, those skilled in the art may make various modifications, improvements and corrections to this specification. Such modifications, improvements and corrections are suggested in this specification, so such modifications, improvements and corrections still belong to the spirit and scope of the exemplary embodiments of this specification.
[0100] At the same time, this specification uses specific words to describe the embodiments of this specification. For example, "one embodiment", "an embodiment", and / or "some embodiments" refer to a certain feature, structure or characteristic related to at least one embodiment of this specification. Therefore, it should be emphasized and noted that "one embodiment" or "an embodiment" or "an alternative embodiment" mentioned twice or more in different positions in this specification does not necessarily refer to the same embodiment. In addition, certain features, structures or characteristics in one or more embodiments of this specification can be appropriately combined.
[0101] In addition, unless explicitly stated in the claims, the order of the processing elements and sequences described in this specification, the use of alphanumeric characters, or the use of other names are not intended to limit the order of the processes and methods of this specification. Although the above disclosure discusses some invention embodiments that are currently considered useful through various examples, it should be understood that such details are only for illustrative purposes, and the attached claims are not limited to the disclosed embodiments. On the contrary, the claims are intended to cover all modifications and equivalent combinations that are consistent with the essence and scope of the embodiments of this specification.
[0102] Similarly, it should be noted that in order to simplify the description disclosed in this specification and thus help understand one or more embodiments of the invention, in the above description of the embodiments of this specification, multiple features are sometimes combined into one embodiment, figure or description thereof. However, this disclosure method does not mean that the features required by the subject matter of this specification are more than the features mentioned in the claims. In fact, the features of the embodiments are less than all the features of the single embodiment disclosed above.
[0103] In some embodiments, numbers describing the number of components and attributes are used. It should be understood that such numbers used in the description of the embodiments are modified by the modifiers "about", "approximately" or "substantially" in some examples. Unless otherwise specified, "about", "approximately" or "substantially" indicate that the numbers are allowed to vary by ±20%. Accordingly, in some embodiments, the numerical parameters used in the specification and claims are approximate values, which may change according to the required features of individual embodiments. In some embodiments, the numerical parameters should take into account the specified significant digits and adopt the general method of retaining digits. Although the numerical domains and parameters used to confirm the breadth of their range in some embodiments of this specification are approximate values, in specific embodiments, the setting of such numerical values is as accurate as possible within the feasible range.
[0104] Each patent, patent application, patent application publication, and other materials, such as articles, books, specifications, publications, documents, etc., cited in this specification are hereby incorporated by reference in their entirety. Except for application history documents that are inconsistent with or conflicting with the contents of this specification, documents that limit the broadest scope of the claims of this specification (currently or later attached to this specification) are also excluded. It should be noted that if the descriptions, definitions, and / or use of terms in the materials attached to this specification are inconsistent or conflicting with the contents described in this specification, the descriptions, definitions, and / or use of terms in this specification shall prevail.
[0105] Finally, it should be understood that the embodiments described in this specification are only used to illustrate the principles of the embodiments of this specification. Other variations may also fall within the scope of this specification. Therefore, as an example and not a limitation, alternative configurations of the embodiments of this specification may be considered consistent with the teachings of this specification. Accordingly, the embodiments of this specification are not limited to the embodiments explicitly introduced and described in this specification.
Claims
1. A method for preparing a carbon-ceramic composite material, characterized in that: The preparation method of the carbon-ceramic composite material comprises the following steps: Evenly mixing silicon carbide, carbon fiber and additives to obtain carbon ceramic prefabricated powder; Placing the carbon ceramic prefabricated powder in a mold of a direct current rapid sintering device, applying a first preparation operation means, and obtaining a sample to be sintered; Starting the heating system of the DC fast sintering device, gradually increasing the DC current for heating, and after heating to the first temperature, applying the second preparation operation means to the sample to be sintered, continuing to increase the DC current, and then gradually heating to the second temperature, and keeping the temperature for a period of time; The heating system is turned off and the mixture is cooled naturally to obtain a carbon-ceramic composite material.
2. The method for preparing the carbon-ceramic composite material according to claim 1, characterized in that: The first preparation method includes: selecting a mold of suitable size, isolating the inside with graphite paper, loading the carbon ceramic prefabricated powder into the mold, applying a pressure of 1MPa-5MPa to pre-compact, and wrapping with heat-insulating carbon felt.
3. The method for preparing the carbon-ceramic composite material according to claim 2, characterized in that: The second preparation operation means comprises: gradually applying pressure to the mold at a pressure increase rate of 1 MPa / min-10 MPa / min, until the pressure reaches 30 MPa-50 MPa.
4. The method for preparing the carbon-ceramic composite material according to claim 1, characterized in that: The auxiliary agent is selected from at least one of Al4SiC, B4C or a metal oxide mixture; Wherein, the metal oxide mixture comprises at least a first metal oxide and a second metal oxide; The first metal oxide is selected from at least one of Al2O3 and Y2O3, The second metal oxide is selected from at least one of MgO, CaO, La2O3, Sc2O3 and Er2O3.
5. The method for preparing the carbon-ceramic composite material according to claim 1, characterized in that: The mass ratio of the silicon carbide, carbon fiber and additive is 1:(0.5-2):(0.01-0.1).
6. The method for preparing the carbon-ceramic composite material according to claim 1, characterized in that: The length of the carbon fiber is 5mm-30mm.
7. The method for preparing the carbon-ceramic composite material according to claim 1, characterized in that: The first temperature range is 700° C., and the heating rate is 50° C. / min-100° C. / min.
8. The method for preparing the carbon-ceramic composite material according to claim 1, characterized in that: The second temperature range is 1600°C-2100°C; the heating rate of gradually heating to the second temperature is 10°C / min-50°C / min; and the insulation time is 20min-2h.
9. A carbon-ceramic composite material, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 8.
10. A carbon ceramic brake disc, characterized in that: The carbon-ceramic composite material is prepared using the method as claimed in claim 9.
Citation Information
Patent Citations
Preparation method for short carbon fiber / silicon carbide composites
CN103204693A
Hydrocyclone wear-resistant ceramic liner and preparation method thereof
CN103922775A
Preparation method of carbon-ceramic composite brake disc
CN106090081A
Method for preparing carbon pottery aircraft brake disc
CN110396000A
Method for rapidly densifying SiC / SiC composite material through flash sintering
CN115894058A